Corporate Restructuring and Labor Productivity Growth - Katariina Hakkala (The Research Institute of Industrial Economics (IUI), 2004)
This paper analyzes corporate restructuring and its role in generating labor productivity growth in a sample of large Swedish manufacturing corporations. It is found that external restructuring, including ownership changes, start-ups and closures of plants, accounted for up to 47 percent of the productivity growth of the sample of corporations during the 1986-96 period. The results indicate that the productivity of large multi-plant corporations grew almost twice as fast as that of single-plant firms with the same internal productivity growth, thanks to their organizational flexibility. Divestitures of low productive plants were found to play a particularly important role in the replacement process generating productivity growth. The effect of external restructuring on productivity is to some extent explained by a shift towards a more skill-intensive production.
Keywords: D24; F23; G34; 330; Corporate Restructuring; Labor Productivity Growth; Arbeitsproduktivität; Organisatorischer Wandel; Schweden